A Comparison of two Multilingual Meeting Systems (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2020)
Multilingual meeting software is still somewhat rare, but at least three systems can provide support to large groups in multiple languages. This paper compares two (Microsoft Live Translator and an academic system called Polyglot). Results show there were no significant differences between the two in terms of perceived translation accuracy, usefulness, ease of use, and design quality. However, Polyglot provides support for more languages (103 versus 66). These and other results are discussed along with directions for future research.